Adolescent and young adult substance use in Australian Indigenous communities: a systematic review of demand control program outcomes - Lynore Geia; Kirstie Broadfield; Daniel Grainger; Andrew Day; Felecia Watkin‐Lui (Elsevier, 2018)
Abstract Objective: Identifying preventative approaches to substance use in Indigenous communities is the foundation for developing evidence‐based responses. This study reports the findings of a systematic review of the published literature evaluating the impact of substance use programs on Australian Indigenous youth. Methods: Evidence about the impact of substance use programs for Indigenous young people was identified from a systematic review of the literature conducted according to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses guidelines. Results: Only four original studies that met the inclusion criteria were identified, although a further 19 papers that described characteristics of programs that may be associated with improved outcomes were reviewed. Conclusions: Evidence relevant to the outcomes of demand control programs that target Australian Indigenous youth substance use is both weak and inconsistent. There is a need to support the type of evaluation activity required to better understand program effectiveness and build the Indigenous knowledge base. Implications for public health: These findings are discussed in relation to the development of evidence‐based practice and the type of knowledge that is likely to be of most use to those seeking to address problems associated with youth substance use.